Aerodynamic Effects of Uniform Blowing and Suction on a NACA4412 Airfoil - Atzori, Marco; Vinuesa, Ricardo; Fahland, Georg; Stroh, Alexander; Gatti, Davide; Frohnapfel, Bettina; Schlatter, Philipp (Flow Turbulence and Combustion, 2020)
We carried out high-fidelity large-eddy simulations to investigate the effects of uniform blowing and uniform suction on the aerodynamic efficiency of a NACA4412 airfoil at the moderate Reynolds number based on chord length and incoming velocity of Rec= 200 , 000. We found that uniform blowing applied at the suction side reduces the aerodynamics efficiency, while uniform suction increases it. This result is due to the combined impact of blowing and suction on skin friction, pressure drag and lift. When applied to the pressure side, uniform blowing improves aerodynamic efficiency. The Reynolds-number dependence of the relative contributions of pressure and friction to the total drag for the reference case is analysed via Reynolds-averaged Navier–Stokes simulations up to Rec= 10 , 000 , 000. The results suggest that our conclusions on the control effect can tentatively be extended to a broader range of Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Active flow control; Aerodynamics; Turbulence simulation; Wing section